In the Words of E. B. White : Quotations from America's Most Companionable of Writers - White, E. B. (Elwyn Brooks), 1899-1985 (Book collections on Project MUSE., 2011)
The author of Charlotte's Web and One Man's Meat, coauthor of The Elements of Style, and columnist for The New Yorker for almost half a century, E.B. White (1899-1985) is an American literary icon. Over the course of his career, White inspired generations of writers and readers with his essays (both serious and humorous), children's literature, and stylistic guidance. In the Words of E.B. White offers readers a delightful selection of "ations, selected and annotated by his granddaughter and literary executor, Martha White. The "ations cover a wide range of subjects and situations, from Automobiles, Babies, Bees, City Life, and College to Spiders, Taxes, Weather, Work, and Worry. E.B. White comments on writing for children, how to tell a major poet from a minor one, and what to do when one becomes hopelessly mired in a sentence. White was apt to address the subject of security by speaking first about a Ferris wheel at the local county fair, or the subject of democracy from the perspective of roofing his barn and looking out across the bay-he had a gift for bringing the abstract firmly into the realm of the everyday. Included here are gems from White's books and essay collections, as well as bits from both published and unpublished letters and journals. This is a book for readers and writers, for those who know E.B. White from his "Notes and Comment" column in The New Yorker, have turned to The Elements of Style for help in crafting a polished sentence, or have loved a spider's assessment of Wilbur as "Some Pig." This distillation of the wit, style, and humanity of one of America's most distinguished essayists of the twentieth century will be a welcome addition to any reader's bookshelf.